The patient with Down syndrome and pulmonary arterial hypertension associated with congenital heart disease: from childhood to adulthood. (3rd October 2022) - Playan Escribano, J; Garrido-Lestache, E; Luna, R; Alvarez Fuente, M; Lopez-Meseguer, M; Guillen Rodriguez, I; Perez Penate, G M; Sabate Rotes, A; Elias Hernandez, T; Lopez Ramon, M; Rueda Soriano, J; Perin, F; et al.
Abstract: : Pulmonary arterial hypertension (PAH) is a common complication of congenital heart disease (CHD) that significantly affects its prognosis. Down syndrome is a common comorbidity among patients with PAH associated with CHD. Children born in recent years with CHD have benefited from advances in pediatric cardiac surgery that have modified their evolution compared to adults with the same pathologies. Our objective was to know and compare the characteristics of the adult and pediatric population with DS and PAH associated with CHD. REHAP and REHIPED are Spanish, voluntary, multicenter registries that include patients with PAH associated with CHD. REHAP started in 2007 and includes patients over 18 years of age. Patients diagnosed with PAH after this time were prospectively included, until 2021. Patients who were followed in the participating centers and diagnosed after January 1998 were retrospectively included in the registry. REHIPED started in 2009 and collects patients between 2 months and 18 years of age. Patients diagnosed with PAH after this time were prospectively included, until 2021. Patients who were followed and diagnosed after January 1998 were retrospectively included. 131 adults and 47 children with DS and PAH associated with CHD were analyzed. Their baseline characteristics, hemodynamics, treatment, and 10-year survival were compared. Adult patients with DS presented more frequently complete atrioventricular canal defect as underlying heart disease and were mostly in Eisenmenger's situation (84%). In pediatric patients the largest group was post-repair PAH (50%). Functional class was similar in both groups, although adults presented significantly greater hemodynamic severity. Regarding medical treatment, no differences were observed between both groups: there was a very low use of prostanoids both at baseline and at follow-up, and a majority use of oral monotherapy. There were no significant differences in survival. Corrective surgery in patients with DS has become more frequent over the years: adults are mostly in Eisenmenger's situation, while post-repair PAH is the most numerous group in children. Although adults show greater hemodynamic severity, survival is similar in both groups. Medical treatment, which showed no differences between pediatric and adult age, is very conservative, with most patients on oral monotherapy and rare use of prostanoids. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Janssen MSD